Effect of multi‐professional education on the perceptions and awareness of oral health care among undergraduate nursing students in a nursing school. Issue 6 (11th February 2021) - Haresaku, Satoru; Kubota, Keiko; Yoshida, Rie; Aoki, Hisae; Nakashima, Fuyuko; Iino, Hidechika; Uchida, Souhei; Miyazono, Mami; Naito, Toru
Abstract: Objective: This study investigates the effects of a study course in oral health care on the perceptions of nursing students. The course was designed and evaluated by a multi‐professional team at a Japanese nursing school. Method: The subjects were 119 nursing students. They participated in the oral health course that comprised 45h of training in 4 years. These were designed and taught by oral health professionals, a certified speech‐hearing therapist, and nurses. Questionnaires were distributed to subjects to compare their perceptions and awareness about oral health care before, in between, and after the courses. A chi‐square test was used to compare the data. Results: After completing the courses, more than 95% of the participants were interested in the oral health care practice and expected to collaborate with oral health professionals after getting qualified. Additionally, they understood the effectiveness of oral health care for the prevention of aspiration pneumonia and perceived that oral health care should be provided to hospitalized patients and community‐dwelling older adults. Their awareness of the need to learn techniques for tooth brushing support, salivary gland massage, oral management, swallowing training, removing tongue coating, and gargling, both in theory and practice, was significantly improved. Conclusion: Multi‐professional education has the potential to improve the awareness of nursing students of oral health care and promote collaborative oral health care in the future.